1996
DOI: 10.2307/2269598
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Lakeshore Residential Development on Coarse Woody Debris in North Temperate Lakes

Abstract: Coarse woody debris (CWD) is a critical input from forested watersheds into aquatic ecosystems. Human activities often reduce the abundance of CWD in fluvial systems, but little is known about human impacts on CWD in lakes. We surveyed 16 north temperate lakes to assess relationships among CWD, riparian vegetation, and shoreline residential development. We found strong positive correlation between CWD density and riparian tree density (r2 = 0.78), and strong negative correlation between CWD density and shoreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
195
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 24 publications
(41 reference statements)
8
195
2
Order By: Relevance
“…Recently, scientists at ELA have shown that removal of macrophyte beds causes reductions in young-of-the-year pike, yellow perch, and pumpkinseed. Christensen et al (1996) found a linear relationship between logs in littoral areas of northern Wisconsin lakes and fish abundance.In many cases, water levels are controlled by dams or weirs at lake outlets, preventing natural fluctuations.…”
Section: Fisheries Managementmentioning
confidence: 90%
“…Recently, scientists at ELA have shown that removal of macrophyte beds causes reductions in young-of-the-year pike, yellow perch, and pumpkinseed. Christensen et al (1996) found a linear relationship between logs in littoral areas of northern Wisconsin lakes and fish abundance.In many cases, water levels are controlled by dams or weirs at lake outlets, preventing natural fluctuations.…”
Section: Fisheries Managementmentioning
confidence: 90%
“…The most obvious impact is road mortality, shown to affect mammals (Philcox et al 1999;Seiler 2005;Grilo et al 2009), birds (Orlowski 2005), reptiles (Iosif et al 2013) and amphibians (Patrick et al 2012). But impacts of roads, traffic and human access can be much more profound, affecting population and community structure (Habib et al 2007), trophic interactions (Kristan III and Boarman 2003;Whittington et al 2011), ecosystem functioning and structure (Christensen et al 1996;Hansen et al 2005;Rentch et al 2005), and environmental conditions through high pollution levels (Hatt et al 2004). Roads can favour the expansion of invasive species (Jodoin et al 2008;Vicente et al 2010), and of exotic and human-favoured predators (Alterio et al 1998).…”
Section: Wilderness Metricsmentioning
confidence: 99%
“…Humans remove wood from river channels to improve recreational and commercial navigation (Angradi et al 2004), to tidy the appearance of shoreline properties (Christensen et al 1996;Francis and Schindler 2006), or to reduce the likelihood of damage to infrastructure. Humans have cut many riparian forests, removing the source of wood to the shore zone (Christensen et al 1996;Angradi et al 2004;Francis and Schindler 2006;Scholten et al 2005). Reservoirs act as traps for wood (Piégay 2003), and stabilized river flows tend to reduce bank-cutting, which is an important source of wood to rivers, as well as reducing the ability of the river to transport wood (Angradi et al 2004).…”
Section: Accumulation and Processing Of Organic Mattermentioning
confidence: 99%